2017
DOI: 10.1186/s40793-017-0253-3
|View full text |Cite
|
Sign up to set email alerts
|

The genome of the cotton bacterial blight pathogen Xanthomonas citri pv. malvacearum strain MSCT1

Abstract: Xanthomonas citri pv. malvacearum is a major pathogen of cotton, Gossypium hirsutum L.. In this study we report the complete genome of the X. citri pv. malvacearum strain MSCT1 assembled from long read DNA sequencing technology. The MSCT1 genome is the first X. citri pv. malvacearum genome with complete coding regions for X. citri pv. malvacearum transcriptional activator-like effectors. In addition functional and structural annotations are presented in this study that will provide a foundation for future path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…Furthermore, RVDs based analysis showed that the six TALEs in Xss-V 2 -18 were identical or nearly identical to plasmid-borne TALEs in Xcm MSCT1, MS14003, H1005 and AR81009 which suggests that these genes may have been horizontally transferred [67,73,74]. The number and location of tal genes varied in the six Xcm strains; MSCT1 possess eight (seven plasmid-borne) [59], XcmH1005 has 12 (six plasmid-and six chromosomallyencoded) [27], XcmN1003 has nine (four plasmidencoded) [27], MS14003 has 8 (7 plasmid-encoded) [46], AR81009 has 12 (six plasmid-encode) [46] and Xss-V 2 -18 has six plasmid-encoded tal genes (Figs. 1, 2).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, RVDs based analysis showed that the six TALEs in Xss-V 2 -18 were identical or nearly identical to plasmid-borne TALEs in Xcm MSCT1, MS14003, H1005 and AR81009 which suggests that these genes may have been horizontally transferred [67,73,74]. The number and location of tal genes varied in the six Xcm strains; MSCT1 possess eight (seven plasmid-borne) [59], XcmH1005 has 12 (six plasmid-and six chromosomallyencoded) [27], XcmN1003 has nine (four plasmidencoded) [27], MS14003 has 8 (7 plasmid-encoded) [46], AR81009 has 12 (six plasmid-encode) [46] and Xss-V 2 -18 has six plasmid-encoded tal genes (Figs. 1, 2).…”
Section: Discussionmentioning
confidence: 98%
“…manihotis, which were identified on plasmids pXAC66, pXcB and pXam46, respectively [67][68][69]. Feyter and Gabriel [28] and Showmaker et al [59] reported the existence of plasmid-borne tal genes in Xcm strains XcmH and MSCT1, respectively. A draft genome sequence of the Xanthomonas translucens pv.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…manihotis, which were identified on plasmids pXAC66, pXcB and pXam46, respectively[62][63][64]. In Xcm, R De Feyter and DWGabriel [27] and KC Showmaker, MA Arick, C-Y Hsu, BE Martin, X Wang, J Jia, MJ Wubben, RL Nichols, TW Allen and DG Peterson[56] reported the existence of plasmid-borne tal genes in strains XcmH and MSCT1.The presence of highly repetitive sequences in tal genes complicates efforts to obtain their nucleotide sequence; therefore, we used a Tn5 insertion method as a sequencing strategy. Normally the number of repeats in tal genes varies between 1.5 and 33.5, and each repeat encodes 33-34 amino acids that vary only at positions 12 and 13 (RVDs) [30].…”
mentioning
confidence: 99%